2010
DOI: 10.1111/j.1439-0507.2009.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Candida albicans and Candida parapsilosis to epithelial cells correlates with fungal cell surface carbohydrates

Abstract: Many studies have described the adherence of Candida albicans to epithelial cells but little is known about Candida parapsilosis adhesion and its role in host cell surface recognition. This study was designed to evaluate the correlation between the adherence of 20 C. albicans and 12 C. parapsilosis strains to human buccal epithelial cells and the expression of fungal cell surface carbohydrates using lectin histochemistry. Adherence assays were carried out by incubating epithelial cells in yeast suspensions (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
(78 reference statements)
2
30
1
Order By: Relevance
“…However, Lima-Neto, et al 14 (2009) showed a higher affinity of C. albicans for epithelial cells than C. parapsilosis , which is in accordance with Repentigny, et al 24 (2000). Although only C. albicans were evaluated in the present study, the findings of the present study show that C. albicans may also be related to chronic periodontal disease, as its adherence was significantly higher.…”
Section: Discussionsupporting
confidence: 65%
“…However, Lima-Neto, et al 14 (2009) showed a higher affinity of C. albicans for epithelial cells than C. parapsilosis , which is in accordance with Repentigny, et al 24 (2000). Although only C. albicans were evaluated in the present study, the findings of the present study show that C. albicans may also be related to chronic periodontal disease, as its adherence was significantly higher.…”
Section: Discussionsupporting
confidence: 65%
“…16,17 This difference could be explained due to the presence of more a-L-fucose residues in the C. albicans cell wall relative to other speices. 18 Interestingly, despite the fact that C. parapsilosis is known to be more a more frequent cause of disease in low birth weight newborns, Falgier et al found that C. parapsilosis showed little capacity to adhere to primary immature human enterocytes compared with C. albicans. 19 Bertini and coworkers previously showed that C. parapsilosis and C. orthopsilosis have similar adhesion capacities to human buccal epithelial cells, in contrast the third member of the C. parapsilosis sensu lato species complex, C. metapsilosis, which displayed a significantly lower adhesive affinity.…”
mentioning
confidence: 99%
“…[26] The earlier in-vitro studies have reported C. albicans to have greater adhesion to oral epithelial cells followed by C. tropicalis and C. parapsilosis. [27,28] The presence of more α-Lfucose remnants promotes greater adhesion of C. albicans. [27] C. albicans is major isolate in healthy subjects on the tongue and buccal mucosa in the present study is in consonance with previous observations.…”
Section: Discussionmentioning
confidence: 99%